Modul Komik Tematik Berbasis Multiple Intellegence untuk Siswa Kelas V Sekolah Dasar - Arnelia Dwi Yasa; Denna Delawanti Chrisyaran; Sa’dun Akbar (Universitas Negeri Malang, 2017)
Abstract: This study aimed to describe the validity of the comic module based on Multiple Intellegence (MI). This research uses research and development approach. Data collected by questionnaire. The data type is the nonverbal data obtained from the expert validation score. The analysis technique used is qualitative data analysis. Qualitative data analysis is derived from inputs, suggestions from expert material validators, language, and instructional design. Expert validation results on teacher guidelines and student modules were 94.67% and 95.04%, respectively. Based on data analysis, student modules and teacher modules developed are very valid. Modules deserve to be used as teaching materials to help students and teachers in the learning process. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kevalidan modul komik tematik berbasis Multiple Intellegence (MI). Penelitian ini menggunakan pendekatan research and development. Data dikumpulkan melalui angket. Jenis data adalah data nonverbal yang diperoleh dari skor validasi ahli. Teknik analisis yang digunakan adalah analisis data kualitatif. Analisis data kualitatif diperoleh dari masukan, saran dari validator ahli materi, bahasa, dan desain pembelajaran. Hasil validasi ahli pada pedoman guru dan modul siswa berturut-turut 94,67% dan 95,04%. Berdasarkan analisis data, modul siswa dan modul guru yang dikembangkan sangat valid. Modul layak digunakan sebagai bahan ajar untuk membantu siswa dan guru pada proses pembelajaran.